Sensorimotor gating impairments induced by MK-801 treatment may be reduced by tolerance effect and by familiarization in monkeys - Saletti, Patricia G.; Maior, Rafael S.; Hori, Etsuro; Nishijo, Hisao; Tomaz, Carlos (Frontiers in Pharmacology, 2015)
Dizocilpine (MK-801) is a noncompetitive NMDA antagonist that induces schizophrenic-like effects. It is therefore widely used in experimental models of schizophrenia including prepulse inhibition (PPI) impairments in rodents. Nevertheless, MK-801 has never been tested in monkeys on a PPI paradigm. In order to evaluate MK-801 effects on monkeys’ PPI, we tested eight capuchin monkeys (Sapajus spp.) using three different doses of MK-801 (0.01; 0.02; 0.03 mg/kg). Results show PPI impairment in acute administration of the highest dose (0.03 mg/kg). PPI impairment induced by MK-801 was reversed by re-exposure to the PPI test throughout treatment trials, in contrast with rodent studies. These results indicate that tolerance effect and familiarization with PPI test may reduce the sensorimotor gating deficits induced by MK-801 in monkeys, suggesting a drug-training interaction.